"A Model for Simulating Photosynthesis in Plant Communities" by W.G. Duncan, R.S. Loomis, W.A. Williams, and R. Hanau, Hilgardia (1967) 38:181–205. Issue 1 (1st January 2019) - Sinclair, Thomas R.
Abstract : This article is part of a series of brief commentaries to highlight papers that have resulted in important and distinctly new perspectives in crop science. A criterion for selection of papers is that they must have been published at least 20 yr ago to allow for a long‐range perspective in assessment of the papers. The current article briefly reviews the paper by W.G. Duncan, R.S. Loomis, W.A. Williams, and R. Hanau published in 1967 that provided original concepts about the interception of solar radiation by crop leaf canopies and the estimate of canopy photosynthesis rate based on the intercepted radiation. They developed a geometric description of beam penetration through leaf layers and calculation of canopy CO2 exchange by considering separately leaves in direct‐beam radiation and in the shade.